Treatment augmentation for posttraumatic stress disorder: A systematic review. Issue 1 (22nd December 2019) - Metcalf, Olivia; Stone, Caleb; Hinton, Mark; O'Donnell, Meaghan; Hopwood, Malcolm; McFarlane, Alexander; Forbes, David; Kartal, Dzenana; Watson, Loretta; Freijah, Isabella; Varker, Tracey
Abstract: This systematic review examined the efficacy of all augmentation approaches for first‐line posttraumatic stress disorder (PTSD) interventions. From 9, 890 records, 34 trials were eligible for inclusion, covering 28 different augmentation approaches. Overall, augmentation approaches were ineffective if they targeted a mechanism similar to the first‐line treatment. Augmentation approaches combining two guideline‐recommended treatments were largely ineffective, reflecting ceiling effects. Pharmacological augmentation approaches targeting fear extinction mechanisms were largely ineffective, or worsened outcomes relative to prolonged exposure alone, as these approaches may inadvertently strengthen fear memories. Augmentation approaches targeting general cognitive enhancement showed promise and provided support for augmentation interventions that require little cognitive or emotional work and target mechanisms different than the first‐line treatment.